Peranan Lembaga Perguruan Seni Beladiri Indonesia Tapak Suci Putera Muhammadiyah Dalam Pembentukan Akhlak Siswa Smk Muhammadiyah 2 BloraTahun Pelajaran 2014/2015 - Sumarno, Marno (2016)
SUMARNO. 0100130045. "THE ROLE OF INDONESIAN MARTIAL ARTS TEACHER SON HOLY SITES IN THE FORMATION OF CHARACTER OF STUDENTS MUHAMMADIYAH SMK Muhammadiyah 2 BLORA OF EDUCATION 2014/2015" Graduate Thesis, University of Muhammadiyah Surakarta, 2015. This study aims to describe the behavior of students SMK Muhammadiyah 2 Yogyakarta, the role of education Martial Arts Prince of the holy sites in the formation of students' moral and positive influence in forming the character of students. This research is a quantitative and qualitative. Data collection methods include observation, interviews, and documentation to collect data on how the implementation of the Prince of the Holy Sites in moral formation of students in SMK Muhammadiyah 2 Yogyakarta. The instrument uses quantitative analysis or analysis of data and kaulitaif based on observations and interviews. Once data is collected, analyzed indukif by displaying the facts on the ground and then given a conclusion by reduction, presentation, and data verification. Based on the quantitative analysis of interpretation are enough. While based on qualitative analysis, a group thesis, the author concludes that the extracurricular activities of the Holy Sites in class X TKJ SMK Muhammadiyah 2 Yogyakarta is compulsory extracurricular already established by the school, so that all tenth grade students must follow during the year up to level two in the level of youth Sacred Sites , Islamic educational activities or called Al-Islam and the implementation of extra-curricular Kemuhammadiyahan is the spirit of the holy site itself. Pendidikan Islam or Al-Islam and Kemuhammadiyahan given before the start of the sport or martial art (martial arts) is a spiritual building, which was held for 60 minutes in order to balance the physical and spiritual interests also include cultivation. With so students can use the knowledge of martial arts with the aim of properly. Where this martial art has a purpose to defend themselves if there is such a threat that can be dangerous for yourself. With the aim of studying martial arts when not accompanied by spiritual guidance because they can harm the students will use the knowledge beladirinya with things that are not good. The creation of fraternity among students as a form that students always pay attention to Al-Islam Those materials and Kemuhammadiyahan they receive extra training for the Holy Sites. Those materials include Al-Islam faith, worship, morality, and the date of the Qur'an, while Kemuhammadiyahaan material about the organization that oversees the organization Muhammadiyah University Martial Arts Indonesia Prince of the Holy Sites.